Notas sobre uma trajetória e os Estudos Culturais - Renato Ortiz (Ciências Sociais Unisinos)
In this article the author reflects on his own work, trying to understand how the problem of culture is treated in his writings. The intellectual trajectory analyzed starts from his doctoral thesis on Afro-Brazilian cults and goes to the texts in which he deals with the relationship between globalization and the mundialization of culture. The background of this reflection is the contrast and dialogue between the way studies on the problem of culture are produced in the social sciences and in a specific area, Cultural Studies.